Characteristics of Red Palm Oil Oleogel Based on Beeswax and Cocoa Butter and Its Application in Red Chocolate Spread - Kurniaditya, Viki Hendi; Setiowati, Arima Diah; Hidayat, Chusnul (agriTECH, 2024)
Red palm oil (RPO) is a product obtained from crude palm oil with a high carotenoid content. Despite the potential, the susceptibility of the constituent β-carotene to degradation and liquid state at room temperature poses a significant challenge to its use by affecting the texture of the final chocolate spread. Several studies have proposed using the oleo gelation technique to overcome this challenge, which regulates the structure of oil and fats mixture using an oleo gelator. Therefore, this study aims to evaluate the physicochemical characteristics of RPO oleogel produced using an oleo gelator from a beeswax and cocoa butter blend. The best product obtained was then applied to produce a red chocolate spread. The results showed that RPO oleogel obtained at a high beeswax-cocoa butter ratio had higher hardness values, β-carotene content, and melting points. In addition, the crystal microstructure of the product was needle-form with larger crystal sizes, leading to a significant increase in the oil binding capacity. Combining 9% beeswax and 1% cocoa butter (BW9-LK1) was the best formula for producing a chocolate spread. The characteristics of the red chocolate spread obtained from the best oleogel were 61.47 brightness level (L*), 5.81 red intensity (a*), and 57.81 yellowish (b*), with an oil binding capacity of 99.95%. The melting temperature was 31.89-41.67 ºC, indicating that it could melt at body temperature and was stable at room temperature. During 5 weeks of storage, the hardness and β-carotene content were 6.016.21 N and 469.07-302.67 ppm, respectively. Based on these results, the oleo gelator from beeswax and cocoa butter blend improved the hardness, melting points, and β-carotene content of RPO oleogel. This indicated that it potentially could be used as an alternative to produce a carotenoid-rich chocolate spread.